Relaxation Technique to Improve Children’s Attention - Agustina, Laelatus Syifa Sari; Supratiwi, Mahardika; Fitriani, Afia (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Nowadays, the new generation is very familiar with technology. The use of gadgets increases the prevalence of the risk of attention deficit disorder and hyperactivity because gadget addiction affects the excessive release of the hormone dopamine, causing a decrease in the maturity of the Pre pre-frontal cortex. Unfortunately, impaired concentration will ultimately have a prolonged impact on a child's academic performance. Symptoms of lack of concentration in children will interfere with cognitive development, behavior, and social and communication skills. One of the factor is the gadget usage. The gadget provided too much stimulus at once, while attention is the ability to focus the mind or mental ability in sorting information that is not needed and focusing only on the required information. Relaxation is a technique believed to help improve attention. Unfortunately, only a few literature present relaxation carried out on children. This research involved 34 children of elementary school in Surakarta. The experiment was carried out using the one-group pre-post test technique. Corsi block and digit span are used as measurement instruments. The results show a significant difference in children's attention ability before and after the intervention.